A Simple and Convenient Method for Simultaneous Determination of Schizandrol A, Schizandrol B, Schisandrin A, γ-Schisandrin, and Schisandrin C - Yu Zhou; Wu Ling Wei; Jiang Xing Hua; Qingsheng Fan (Journal of Chemistry)
A simple, rapid, and specific HPLC method was established for simultaneous determination of five major lignans (Schizandrol A, Schizandrol B, Schisandrin A, γ-Schisandrin, and Schisandrin C) in Schisandra chinensis. The five lignans can be separated completely on Kromasil C18 column (250 nm × 4.6 nm) and then detected at 254 nm using methanol (mobile phase A) and water (mobile phase B) with gradient elution as the mobile phase at 1.0 mL/min flow rate. The column temperature was 30°C. The method was validated in terms of linearity, precision, stability, repeatability, and recovery. Results showed that the method is accurate and reproducible.